Comparison of Umbilical Cord Cleansing Using Sterile Water and Povidine Iodine-Spirit During Early Neonatal Period: A Double Blind Randomized Control Trial - Chawla, Gautam (J Clin Diagn Res, 2015)
AIM: To compare the effect of umbilical cord care with Povidine Iodine- Spirit on umbilical infection in early neonatal period. MATERIALS AND METHODS: Prospective double blinded randomized controlled study was undertaken to evaluate the effect of daily cleansing of the umbilical cord of term infants with Spirit (Alcohol) –Povidine Iodine combination). This was also compared to the retrospective data obtained for the prevailing practice of keeping the umbilical cord dry. RESULTS: 1518 infants were included in the study. (462 in the “cord care group”, 496 in the “water” placebo group, & 560 in “Dry” retrospective group). There was an overall reduction in the clinically screened and evaluated “umbilical infection” in the Povidine –Iodine group. This was attributable to a greater reduction in the mixed bacterial (Colonizer/ commensals) isolates. The Relative Risk for Staph. aureus was lesser when the cord was kept dry (RR 0.6, p<0.01) and sterile water (Placebo) group (RR 0.7, p<0.01). CONCLUSION: Avoiding the antiseptic cleansing increased the RR for commensal / mixed bacterial over growth that would probably facilitate umbilical cord separation.